(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
The article examines innovative and interdisciplinary approaches to studying A. P. Chekhov’s play The Seagull. It demonstrates how the integration of literary, psychological, cultural, and digital analysis makes literature instruction more meaningful and responsive to contemporary educational needs. Examples of interactive and projectbased methods for working with the text are provided, aimed at developing students’ critical thinking as well as their creative and research skills.